Pre-Service Teacher Education in India: Some Apposite Issues - Joshi, Dr. Dhananjay; Chabra, Dr. Sonal; Dutta, Dr. Indrajeet (Voices of Teachers and Teacher Educators, 2020)
Teacher quality and educating high-quality teachers have emerged as the fundamental problems to be solved by nations since the correlation between education and economy is becoming more apparent, and the principal factor in student achievement is teacher quality (Cochran-Smith, 2008). Teacher quality has been a continual issue in the field of education (Wang, 2011). Considering teacher education as the bedrock for the national development of our country, the issues gripping teacher education deserve attention from all the stakeholders. In this paper, the writers have made a modest attempt to highlight the concerns gripping one of the largest teacher education systems of the world.